Community Socialization and Empowerment through Pineapple Stick Processing and Marketing in Jurusen Village, Central Aceh: Sosialisasi dan Pemberdayaan Masyarakat melalui Pengolahan Stik Nanas dan Pemasarannya di Desa Jurusen Aceh Tengah - Anna Permatasari Kamarudin; Ratna Dewi; Lenawati Asry; Rahmadi Asri; Abd Jalil; Amna Amna (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Jurusen Village is one of the main pineapple-producing areas in Pegasing, Central Aceh. However, pineapples are predominantly sold fresh, which poses a high risk of post-harvest losses due to their perishable nature. Processing pineapples into more durable products, such as pineapple sticks, offers a potential solution to increase value and reduce losses. This community service program aimed to empower housewives by providing socialization and introductory training on processing fresh pineapples into pineapple sticks to enhance added value and income potential.The program employed a socialization-based approach involving 14 housewives affiliated with the local Majelis Taklim. Activities included lectures, discussions, and evaluations using pre-test and post-test instruments to assess knowledge changes, complemented by participant satisfaction surveys.The results showed a measurable increase in participants’ knowledge, with post-test scores improving by approximately 28–78% compared to pre-test results. Participants also recognized the potential of processed pineapple products as culinary items and local souvenirs that could contribute to household income. Evaluation results indicated high satisfaction, particularly regarding the relevance, clarity, and usefulness of the materials. The program effectively enhanced participants’ knowledge and awareness of pineapple processing as an initial step toward sustainable community empowerment. Further technical training and marketing assistance are recommended to support commercialization.